(untitled) (Revista Contexto & Saúde, 2026)
Aim: to identify the factors affecting the welcoming of transgender people from the perspective of Primary Health Care nurses. Methodology: This is a descriptive and qualitative study. The research was conducted with 13 nurses from Family Health Strategy units in a municipality in the hinterland of Paraíba, Brazil, during the year 2022. Data for this study were obtained through semi-structured interviews and analyzed based on the Collective Subject Discourse technique. Results: From the nurses’ discourse, two categories of analysis were constructed: Nurses’ perceptions of the barriers to welcoming the transgender population and Continuing education: a possibility for re-signifying the welcoming of trans people. Conclusion: The study identified factors that influence the welcoming of transgender people from the nurses’ perspective. It was found that, although it is essential in Primary Care, this stage has gaps that hinder the establishment of bonds and progress in the consultation.